Following the Pulsations in the Long-term Cooling of GW Librae and V386 Serpentis - Paula Szkody; Jan van Roestel; Keaton J. Bell; Zachary P. Vanderbosch; Anjum Mukadam; Simone Scaringi (The Astronomical Journal, 2024)
GW Lib and V386 Ser are dwarf novae systems containing pulsating white dwarfs that underwent large 8–9 mag amplitude outbursts in 2007 and 2019, respectively. Following the pulsation periods in these systems after the outburst provides a means to view the heating and cooling effects of mass accretion on the instability region of the white dwarf. Follow-up optical observations during 2021–2023 for these two systems are reported, resulting in a time span coverage of 16 yr for GW Lib and 4 yr for V386 Ser after their outbursts that reveal large differences in behavior as their white dwarfs returned to quiescence. GW Lib showed intermittent longer periods at 19 minutes, 1.4, 2, and 4 hr during the first 16 yr after the outburst, before finally showing, at 14 yr post-outburst, two of the three short-period modes apparent during preoutburst quiescence. In contrast, V386 Ser appeared to follow theoretical expectations, showing a shorter-period pulsation soon after the outburst, and progressively longer periods as it cooled to its quiescent state. While the optical light returns to quiescent value within 2 yr, it is apparent that the white dwarf takes much longer to recover to its quiescent state. Theoretical work is needed to explain the large differences in otherwise similar systems.